A multi-layer composite antibacterial dressing with high liquid absorption

CN122581970BActive Publication Date: 2026-10-20SHAOXING FUQING HEALTH PROD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611088741.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20
Estimated Expiration
2046-07-22

AI Technical Summary

Technical Problem

然而,在高渗出或外界受压条件下,该类敷料往往难以兼顾快速导液与抑制液体回渗,普遍存在液体滞留时间长及管理效率不足等问题

Benefits of technology

[0020]本申请将功能化接触层与高吸液容量的吸收层进行结构复合,并在层间构建合理的稳定界面结构,在保持抗菌功能的同时基础上,在敷料内部构建由接触层至吸收层逐级变化的润湿梯度与毛细压力梯度,实现伤口渗出液的分级调控,确保渗出液由创面侧向远离创面侧的单向传导,实现对伤口渗出液的有效调控,完成渗出液的快速导入与内部锁存,可显著缩短液体在接触层的滞留时间,降低局部组织浸渍风险,维持创面表面的相对干爽及稳定微环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122581970B_ABST
    Figure CN122581970B_ABST
Patent Text Reader

Abstract

The application provides a multi-layer composite antibacterial dressing with high liquid absorption efficiency, and belongs to the technical field of medical dressings. Any one of QSA dressing, QOSA / CMCS dressing and QSA / DHQ dressing is used as a contact layer, a needle-punched absorbent pad is used as an absorption layer, and a multi-layer composite antibacterial dressing with high liquid absorption efficiency is constructed through interlayer compounding. The multi-layer composite antibacterial dressing of the application can realize controllable liquid transmission direction, is helpful for the synergistic regulation and control of the introduction, diffusion and storage process of exudates, and can improve the overall management efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a highly absorbent, multi-layered composite antibacterial dressing, belonging to the field of medical dressing technology. Background Technology

[0002] In clinical wound care, effective management of wound exudate is crucial for maintaining the homeostasis of the healing microenvironment. Wound exudate production exhibits significant dynamic fluctuations and phased characteristics, especially in highly exudative wounds such as chronic ulcers and deep burns, where the exudate volume is large and the duration is prolonged. If the dressing cannot efficiently absorb and properly disperse the excessive exudate within a short time, the fluid tends to stagnate at the wound-dressing interface, leading to problems such as tissue maceration and bacterial overgrowth, thus delaying the healing process.

[0003] Traditional wound dressings primarily rely on the material's own absorbency to passively manage exudate. However, under conditions of high exudation or external pressure, these dressings often struggle to simultaneously achieve rapid fluid drainage and inhibit backflow, resulting in problems such as long fluid retention times and insufficient management efficiency. Summary of the Invention

[0004] In view of this, this application provides a highly absorbent multilayer composite antibacterial dressing that enables controllable liquid transport direction, which helps to coordinate the introduction, diffusion and storage of exudate, thereby improving overall management efficiency.

[0005] Specifically, this application is implemented through the following scheme: A highly absorbent multilayer composite antibacterial dressing uses any one of QSA dressing, QOSA / CMCS dressing, or QSA / DHQ dressing as the contact layer and a needle-punched absorbent pad as the absorbent layer, and constructs a highly absorbent multilayer composite antibacterial dressing through interlayer composite.

[0006] Furthermore, as a preferred option: The pore size of the contact layer is 17.5–29.5 µm.

[0007] The needle-punched absorbent pad is prepared as follows: In S1, the fibers are further opened, combed, and oriented in the carding machine to form a fiber web, ensuring that the quality of each type of fiber entering the carding machine remains consistent. After initial consolidation in the pre-needling zone, the fiber web enters the main needle-punching zone, where the main needles and barbs work together to double-sided entanglement and reinforcement, resulting in a single-fiber nonwoven fabric corresponding to each type of fiber. Through the shaping in the pre-needling zone and the reinforcement in the main needle-punching zone, the loose fiber web gradually becomes denser and forms a structurally stable single-fiber nonwoven fabric.

[0008] S2, each single-fiber nonwoven fabric is stacked and then needle-punched again to obtain a needle-punched absorbent pad.

[0009] In S1, The parameters for the combing process are set as follows: cylinder speed 35–45 r / min, doffer speed 8–12 r / min, fiber feed rate 5–15 m / min, upper and lower curtain conveying speeds both 8–15 m / min, and matte curtain speed 3–6 m / min. More preferably, the cylinder speed is 40–42 r / min, doffer speed 9–10 r / min, fiber feed rate 8–10 m / min, upper and lower curtain conveying speeds both 10–12 m / min, and matte curtain speed 5–6 m / min.

[0010] The parameters of the pre-needling zone are set as follows: needle punching frequency of 10-20 times / min, fiber web feeding speed of 5-20 m / min, and discharge speed of 5-20 m / min. More preferably, the needle punching frequency is 10-13 times / min, the fiber web feeding speed is 12-16 m / min, and the discharge speed is 12-16 m / min, and the discharge speed is not lower than the feeding speed.

[0011] The parameters of the main needle-punching area are set as follows: main needle-punching frequency 20-35 times / min, barb frequency 20-35 times / min, feeding speed 15-20 m / min, and discharging speed 15-20 m / min.

[0012] In S2, the parameters for the second needle piercing are set as follows: the pre-piercing frequency is 10-15 times / min, the feeding speed is 10-20 m / min, and the discharge speed is 10-20 m / min; the frequencies of the main piercing and the barbs are 30-35 times / min and 30-35 times / min, respectively, and the feeding and discharge speeds are both 15-20 m / min.

[0013] The fiber includes at least one of viscose fiber and hydroxymethyl cellulose fiber. More preferably, the viscose fiber includes at least two finenesses, with a fineness of 1 to 2 dtex. The hydroxymethyl cellulose fiber has a fineness of 1 to 1.5 dtex.

[0014] The absorbent layer includes an intermediate layer formed of hydroxymethyl cellulose fibers and two viscose fiber layers located on both sides of the intermediate layer. Viscose fiber layer one contains viscose fibers of at least two finenesses, and the fineness decreases from the outside to the inside (the side closer to the intermediate layer is the inside, and the opposite side is the outside). Viscose fiber layer two contains viscose fibers of at least two finenesses, and the fineness decreases from the outside to the inside (the side closer to the intermediate layer is the inside, and the opposite side is the outside).

[0015] The preparation method of the QSA dressing is as follows: QSA powder is dissolved in deionized water to obtain a solution with a concentration of 8-15 wt%, which is then sprayed onto the surface of a cotton nonwoven fabric, left to stand, and dried to obtain the QSA dressing.

[0016] The preparation method of the QOSA / CMCS dressing is as follows: carboxymethyl chitosan (CMCS) powder is dissolved in deionized water, then QOSA powder is added and stirred until completely dissolved to obtain a composite solution with a CMCS concentration of 2-3 wt% and a QOSA concentration of 2-3 wt%. The composite solution is sprayed onto the surface of cotton nonwoven fabric, left to stand, and dried to obtain the QOSA / CMCS dressing.

[0017] The preparation method of the QSA / DHQ dressing is as follows: Dihydroquercetin (DHQ) powder is dissolved in deionized water, then QSA powder is added and stirred until completely dissolved to obtain a composite solution with DHQ concentration of 2-3 wt% and QSA concentration of 4-8 wt%. The composite solution is sprayed onto the surface of cotton nonwoven fabric, left to stand, and dried to obtain the QSA / DHQ dressing.

[0018] In the interlayer lamination process, pressure bonding is performed using a lattice-arranged pressing column, with an applied pressure of 50–300 kPa and a pressing duration of 10–30 s. More preferably, the pressing column is a cylindrical or square column. The lattice arrangement refers to the arrangement of multiple pressing columns in a staggered, aligned, or random manner.

[0019] An adhesive layer is also provided between the contact layer and the absorption layer. The adhesive layer is obtained by drying and solidifying an SA solution with a concentration of 1 to 2 wt%.

[0020] This application structurally combines a functionalized contact layer with a high absorbent layer and constructs a reasonable and stable interface structure between the layers. While maintaining antibacterial function, it constructs a wetting gradient and capillary pressure gradient that gradually changes from the contact layer to the absorbent layer within the dressing, thereby achieving graded regulation of wound exudate. This ensures unidirectional conduction of exudate from the wound side to the side away from the wound, effectively regulating wound exudate, and completing the rapid introduction and internal locking of exudate. It can significantly shorten the residence time of liquid in the contact layer, reduce the risk of local tissue maceration, and maintain a relatively dry and stable microenvironment on the wound surface. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application.

[0022] Figure 1 This is a schematic diagram of the structure of the dressing in this application.

[0023] Figure 2 This is a schematic diagram of the absorption layer in this application.

[0024] Figure 3A schematic diagram of the process for constructing a highly absorbent, multi-layered composite antibacterial dressing for this application.

[0025] Figure 4 This is a three-dimensional structural diagram of the composite device in this application.

[0026] Figure 5 This is a top-view structural diagram of the composite device in this application.

[0027] Figure 6 The figure shows the dot matrix distribution of the composite device of this application. Part (a) is dot matrix one, part (b) is dot matrix two, part (c) is dot matrix three, part (d) is dot matrix four, part (e) is dot matrix five, part (f) is dot matrix six, part (g) is dot matrix seven, and part (h) is dot matrix eight.

[0028] The following are the labels in the diagram: 1. Contact layer; 2. Absorbing layer; 21. Intermediate layer; 22. First outer side; 221. Part B; 222. Part A; 23. Second outer side; 3. Pore; 4. Grip part; 5. Pressing part; 6. Dot matrix part; 61. Pressing column one; 62. Pressing column two; 7. Applying pressure part.

[0029] Figure 7 To illustrate the moisture-wicking properties of the absorbent layer in this application, part (a) in the figure shows the unidirectional moisture-wicking index of the needle-punched absorbent pad; part (b) shows the liquid absorption process of the needle-punched absorbent pad.

[0030] Figure 8 To illustrate the effects of different adhesive parameters, part (a) of the figure shows different adhesive structures at a 1% SA concentration; part (b) shows different adhesive structures at a 2% SA concentration; part (c) shows the real-time peel strength of a square structure at a 1% SA concentration; and part (d) shows the real-time peel strength of a circular structure at a 1% SA concentration.

[0031] Figure 9 To demonstrate the peel strength properties of the dressing of this application, part (a) in the figure represents the peel strength; part (b) represents the tensile breaking strength; part (c) represents the peel process curve; and part (d) represents the tensile deformation process with different orientations.

[0032] Figure 10 The image shows SEM images of the dressings used in this application. Part (a) is BATTAB; part (b) is BATTAB / QSA; part (c) is BATTAB / QOSA / CMCS; and part (d) is BATTAB / QSA / DHQ.

[0033] Figure 11The figures show the pore size distribution and physical morphology of the dressings of this application. Part (a) is BATTAB / QSA; part (b) is BATTAB / QOSA / CMC; part (c) is BATTAB / QSA / DHQ; and parts (d) to (g) are physical images of BATTAB puncture absorbent pad, BATTAB / QSA, BATTAB / QOSA / CM, and BATTAB / QSA / DHQ.

[0034] Figure 12 To illustrate the water absorption properties of single-layer and multi-layer composite dressings, part (a) of the figure shows the swelling curve in PBS solution; part (b) shows the absorption amount in deionized water and PBS solution. Detailed Implementation

[0035] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit the technical solutions of this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without creative effort are within the scope of protection of this application.

[0036] The terms and their corresponding abbreviations used in this application are as follows: Sodium Alginate (SA).

[0037] Oxidized Sodium Alginate (OSA).

[0038] Quaternized alginate: Quaternized alginate, QSA.

[0039] Quaternized oxidized sodium alginate (QOSA)

[0040] Carboxymethyl chitosan (CMCS)

[0041] Dihydroquercetin (DHQ)

[0042] In this embodiment: 1) Preparation method of QSA: Dissolve sodium alginate in distilled water and stir thoroughly until completely dissolved. Add 2,3-epoxypropyltrimethylammonium chloride and stir evenly. Place in a stirrer to react in the dark. After the reaction is completed, adjust the pH to below 7 to terminate the cationization process, and then place at room temperature. Add ethanol to precipitate, filter, collect the product and dry it. The mass ratio of sodium alginate to 2,3-epoxypropyltrimethylammonium chloride is 1:1.5.

[0043] 2) Preparation method of QOSA: Weigh the QSA prepared by the above method, dissolve it in distilled water and stir until it is completely dissolved, add sodium periodate to react in the dark, then add ethylene glycol to terminate the reaction, place at room temperature, dialyze in deionized water with a 3500 Da dialysis bag, and freeze dry to obtain QOSA.

[0044] 3) DHQ: Purity > 98%, Chengdu Ruifenside Biotechnology Co., Ltd.; 1,1-Diphenyl-2-picrylhydrazine (DPPH): Purity ≥ 97%, Shanghai Aladdin Biochemical Technology Co., Ltd.; 3-Ethylbenzothiazoline-6-sulfonic acid (ABTS): Analytical grade, Sinopharm Group Chemical Reagent Co., Ltd.; Potassium persulfate: Purity ≥ 99.5%, Sinopharm Group Chemical Reagent Co., Ltd.

[0045] 4) In the absorbent layer: viscose fiber, Zhejiang Baorenhe Zhong Technology Co., Ltd., with specifications of 1.1 dtex*38 mm, 1.3 dtex*38 mm and 1.7 dtex*38 mm, denoted as A, B and C respectively. Carboxymethyl cellulose fiber (1.3 dtex*38 mm), Zhejiang Zhende Medical Supplies Co., Ltd., denoted as T.

[0046] This embodiment provides a highly absorbent, multi-layered composite antibacterial dressing, combined with... Figure 1 It includes a contact layer 1 and an absorbent layer 2. The contact layer 1 is made of QSA dressing (15wt%QSA, denoted as 15wt%QSA), QOSA / CMCS dressing (3wt%QOSA, 3wt%CMCS, denoted as Q3C3), or QSA / DHQ dressing (8wt%QSA, 3wt%DHQ, denoted as 8%Q-3). The absorbent layer 2 is a needle-punched absorbent pad.

[0047] The above dressings are prepared in the following manner: Step 1, Prepare absorber layer 2: S1 uses a needle-punching process to prepare the absorbent layer nonwoven material. The process flow is as follows: opening, carding, web laying, pre-punching, main punching, barbing, and winding. Each type of fiber first undergoes an opening treatment before entering the carding process, where it undergoes further opening, carding, and orientation in the carding machine to form a uniform fiber web. During the preparation process, the fiber quality of each type of fiber entering the carding machine is kept consistent. The carding process parameters are as follows: cylinder speed is 40.44 r / min, doffer speed is 9.98 r / min, feed speed is 8.84 m / min, upper and lower curtain conveyor speeds are both 10.05 m / min, and matte curtain speed is 5.33 m / min.

[0048] In step S2, the formed fiber web first enters the pre-needling zone for initial consolidation. The needle-punching frequency during the pre-punching stage is 11.07 times / min, the feed rate is 15.82 m / min, and the discharge rate is 15.83 m / min. Subsequently, the fiber web enters the main needle-punching zone at a conveying speed of 15.78 m / min. In the main needle-punching stage, the fiber web is double-sided entangled and reinforced through the synergistic action of the main needles and barbs. The main needle-punching frequency is 31.07 times / min, the barb frequency is 31.21 times / min, and the feed and discharge rates are 16.28 m / min. Through pre-punching and main needle-punching reinforcement, the loose fiber web gradually becomes denser and forms a structurally stable single-fiber needle-punched nonwoven fabric.

[0049] S3. Based on this, different single-fiber base fabrics are layered according to the designed structure and then needle-punched for reinforcement. During the layering and needle-punching stage, the pre-punching frequency is 11.07 times / min, the feed rate is 15.82 m / min, the discharge rate is 15.83 m / min, the main punching and barb punching frequencies are 31.07 times / min and 31.21 times / min respectively, and the feed and discharge rates are 16.28 m / min. Various needle-punched absorbent pads with different structures are prepared through the above process.

[0050] Based on the different combinations and number of layers of single-fiber needle-punched nonwoven fabrics, six types of needle-punched absorbent pads with structures of BAAB, BATTAB, CAAC, CATTAC, CBAABC, and CBATTABC were finally prepared.

[0051] Specifically, taking BATTAB as an example, its cross-sectional structure can be described as follows: Figure 2 As shown: It includes an intermediate layer 21, a first outer layer 22, and a second outer layer 23. The intermediate layer 21 is composed of a single-fiber base fabric formed by two layers of carboxymethyl cellulose fibers. The first outer layer 22 and the second outer layer 23 are symmetrically distributed on both sides of the intermediate layer 21 and have the same structure, both consisting of part A and part B. The fiber fineness forming part B is greater than that forming part A. The fiber fineness forming part B is 1.3 dtex, and the fiber fineness forming part A is 1.1 dtex.

[0052] The remaining five structures, BAAB, CAAC, CATTAC, CBAABC, and CBATTABC, are similar to BATTAB.

[0053] Step 2, lamination: The composite process is as follows Figure 3 As shown in part (a): A 1 wt% SA solution was prepared as an adhesive. The SA solution was applied to the dot matrix part 6 of the composite device and pressed onto the absorbent layer 2. The SA solution covered the surface of the absorbent layer 2 and the pores 3. A contact layer 1 was then applied to the surface of the absorbent layer 2, and the composite was performed by pressing with the pressing part 5. The pressure applied during the composite process was 100 kPa, and the pressing time was 15 s. The dressing was dried, and the resulting multilayer composite dressing was placed in a constant temperature and humidity environment for 24 h. The resulting dressings were designated as BATTAB / QSA, BATTAB / QOSA / CMCS, and BATTAB / QSA / DHQ, respectively.

[0054] Taking the molding process of QSA / DHQ dressings as an example, combined with Figure 3 As shown in part (b): Weigh 0.281 g of DHQ (structural formula see...) Figure 3 Dissolve the powder (part (c)) in 50 mL of deionized water, heat and stir until fully dissolved, and stop heating after DHQ is completely dissolved. Add 4 g of QSA (structural formula see [link]). Figure 3 The powder from part (d) was stirred thoroughly until completely dissolved to obtain a QSA / DHQ composite solution. Subsequently, the mixed solution was uniformly sprayed onto the surface of a cotton nonwoven fabric. After spraying, it was allowed to stand for 5 minutes to ensure full absorption of the solution, then placed in an oven to dry and store, yielding a QSA / DHQ dressing (8% Q-3 dressing).

[0055] The forming process for QSA dressings and QOSA / CMCS dressings is the same as that for QSA / DHQ dressings.

[0056] The structure of the composite device is as follows: Figure 4 , Figure 5 As shown: It mainly includes a gripping part 4, a pressing part 5, and a dot matrix part 6. The pressing part 5 and the dot matrix part 6 are located at opposite ends of the gripping part 4. The dot matrix part 6 is further divided into two parts: one part contains a pressing post 61, and the other part contains a pressing post 62. The pressing post 61 and the pressing post 62 are pressing posts of different shapes, so that at least two shapes of pores 3 can be generated by the same composite transposition. Figure 4 As shown, pressing post 61 is cylindrical and pressing post 62 is square.

[0057] Pressing pin 61 and pressing pin 62 can use the same dot matrix distribution or different dot matrix distributions. The dot matrix distribution can be staggered or aligned, such as... Figure 6 As shown in the figure, (a) to (h) are respectively 6-5-6-5-6 (abbreviated as 6-5), 4-4-4-4 (abbreviated as 4-4), 4-3-4-3-4 (abbreviated as 4-3), 3-2-3-2-3 (abbreviated as 3-2), 6-6-6-6-6, 5-5-5-5-5, 4-4-4-4-4, 3-3-3-3-3.

[0058] The pressing part 5 is 10×10cm in size and has a flat plate structure; the dot matrix part 6 is 8×8cm in size, the diameter of the first pressing post 61 is 1cm, and the side length of the second pressing post 62 is 1cm.

[0059] The dressings obtained by the above methods were characterized and tested: (a) Mechanical property testing of needle-punched absorbent pads Test method: The tensile properties of the needle-punched absorbent pad were tested using a universal testing machine (Instron, USA, 3365). The tensile clamping distance was 4.5 cm, the tensile speed was 100 mm / min, and the sample width was 5 cm.

[0060] Referring to Table 1, the six types of needle-punched absorbent pads exhibit significant differences in tensile strain and maximum load performance. The CBATTABC and BATTAB combinations demonstrate high tensile strain (48.34% and 47.07%, respectively) and good deformation adaptability, while their maximum loads (43.29 N and 42.23 N, respectively) show excellent load-bearing capacity, making them suitable for applications with high liquid absorption or high strength requirements. In contrast, the other combinations show relatively lower tensile strain and maximum load, indicating limited flexibility and load-bearing capacity.

[0061] Table 1: Mechanical Properties of Needle-Punched Absorbent Pads .

[0062] (II) Performance of Needle-Punched Absorbent Pads (1) Porosity Test Method: The porosity of the prepared needle-punched absorbent pad material was measured using a thickness gauge (Wenzhou Darong, YG141D) at a pressure of 0.1 kPa. Five measurements were taken, and the average value was used. The porosity was determined according to GB / T42697-2023 "Test Method for Porosity of Nonwoven Fabrics". n (%) Formula calculation: .

[0063] In the formula, n is the porosity; m is the areal density of the needle-punched absorbent pad, g / m³. 2 ; t is the thickness of the needle-punched absorbent pad, in cm; ρ is the fiber density of the needle-punched absorbent pad, in g / cm³. 3 .

[0064] (2) Air permeability test: The air permeability of the needle-punched absorbent pad was tested using an air permeability tester (Roaches, RT5300). The test pressure was 200 Pa, and the test area was 20 cm². 2 .

[0065] (3) MMT Test: To quantitatively evaluate the directional liquid absorption performance of needle-punched absorbent pads, a liquid moisture management tester (MMT, EY60, Hong Kong) was used to test the samples. The test solution was a 0.9 wt% sodium chloride solution to simulate the environment of human exudate. By measuring the moisture absorption rate and liquid transport behavior of the upper and lower surfaces of the material, the unidirectional transfer index was calculated to characterize the difference in the dressing's unidirectional moisture-wicking ability. The test process was strictly carried out in accordance with GB / T 21655.2-2019 "Evaluation of the moisture absorption and quick-drying properties of textiles - Part 2: Dynamic Moisture Transfer Method".

[0066] (4) Staining water droplet test: A 0.9 wt% sodium chloride solution was stained with blue ink and dropped onto the surface of the needle-punched absorbent pad. The state of the water droplets was observed, and the staining on both sides of the dressing was recorded.

[0067] The porosity and permeability test results are shown in Table 2. CATTAC and BATTAB had relatively high porosities, at 94.8% and 89.5%, respectively, while CBAABC had the lowest porosity at 71.5%, possibly due to less variation in fiber fineness and a denser fiber packing. Overall, samples with higher porosity showed better permeability, while samples with denser structures exhibited significantly reduced permeability. BATTAB maintained a relative balance between pore connectivity and wet structural stability, possessing both high liquid absorption and conductivity while avoiding insufficient structural support due to excessive porosity.

[0068] Table 2: Porosity and air permeability of needle-punched absorbent pads .

[0069] Table 2 shows that CATTAC and BATTAB have relatively high porosities, at 94.8% and 89.5% respectively, while CBAABC has the lowest porosity at 71.5%, possibly due to less variation in fiber fineness and a denser fiber packing. Overall, samples with higher porosity exhibit better air permeability, while samples with denser structures show significantly reduced air permeability. BATTAB maintains a relative balance between pore connectivity and wet structural stability, possessing both high liquid absorption and conductivity while avoiding insufficient structural support due to excessive porosity.

[0070] Moisture-wicking properties and liquid absorbency, such as Figure 7As shown: The composite antibacterial dressing of this application adopts a functional layered structure design, with an inner antibacterial contact layer 1 and an outer needle-punched nonwoven absorbent layer 2. The differences in fiber composition, pore structure, and surface wettability between the two layers facilitate the rapid introduction of liquid from the contact layer into the absorbent layer, where it diffuses and is stored. The unidirectional transfer index is used to quantitatively characterize the difference in moisture absorption capacity between the two sides of the material; a higher value indicates stronger directional moisture-wicking performance. Figure 7 As shown in section (a), all needle-punched absorbent pads exhibited good directional liquid absorption performance, indicating that the three-dimensional interconnected pore structure formed by needle punching is conducive to rapid liquid transport and storage. Among them, the BATTAB sample had the highest unidirectional transfer index of 227.7, higher than other absorbent pads, indicating that its unidirectional liquid migration ability was optimal. According to GB / T 21655.2-2019 "Evaluation of the Moisture Absorption and Quick-Drying Properties of Textiles - Part 2: Dynamic Moisture Transfer Method", the directional liquid absorption performance of this sample reached level four (the highest being level five), exceeding the level three benchmark specified in the standard, and meeting the requirements for high-performance moisture-wicking materials. Figure 7 The dyeing droplet experiment in part (b) shows that the droplets are rapidly absorbed by the fiber network upon contact and diffuse quickly and uniformly along the plane of the material, indicating that the material has good lateral liquid conduction ability. The BATTAB diffusion process is the most concentrated, which is consistent with its high unidirectional transfer index.

[0071] (III) Peel strength test of multilayer composite dressing Test method: Referring to the medical nonwoven wound absorbent pad standard T / YNIA 030-2025, the interlayer peel strength of the multilayer composite dressing was tested using a universal testing machine (Instron, USA, 3365). The peel gap was 15 mm, the tensile speed was 100 mm / min, the tensile length was 10 cm, and the sample width was 5 cm.

[0072] Based on adhesive performance testing and practical application requirements, the optimal adhesive process was screened, focusing on interfacial bonding strength and structural stability. Following the medical nonwoven wound absorbent pad standard T / YNIA 030-2025, a peel strength consistently above 1 N / 5 cm was used as the basic criterion to screen composite structures that balance absorbency and breathability. Preliminary experiments were conducted using BATTAB and 8% Q-3 dressings to investigate the effects of SA concentration and compression technique on peel performance. Results are as follows: Figure 8 (In the diagram, F and Y represent square and cylindrical pressure posts, respectively.) As shown: Under the same pressure conditions, increasing the SA concentration from 1 wt% to 2 wt% can enhance interfacial bonding, but it can also lead to localized solidification of the absorbent layer, which is not conducive to rapid liquid transport. In contrast, under the 1 wt% SA condition, the peel strength of all composite dressings meets the standard requirements, and the impact on the absorbent layer structure is relatively small (see...). Figure 8(a) and (b) of the text). Regarding the pressing shape, the square structure exhibits higher and more stable peel strength than the round structure (see...). Figure 8 (c) and (d) in the text.

[0073] Further analysis Figure 8 The peel curves in sections (c) and (d) show that structures with dense bonding points exhibit a longer, more stable plateau region, while structures with too few bonding points are prone to fluctuations and poor interfacial stability. The 4-3 distribution structure exhibits a smooth peel curve (i.e., the curves corresponding to SA-1%-F-4 and SA-1%-Y-4), with continuous interfacial separation and optimal bonding uniformity. Considering the requirements for liquid absorption performance, pore structure preservation, and air permeability, excessively high peel strength is not optimal. A moderate and stable interfacial bond should be achieved while meeting the standards and effectively reducing the compaction effect on the fiber network. This approach is most beneficial for maintaining the pore structure and air permeability of the absorbent layer. Therefore, the optimal bonding process was determined to be a square-pressed 4-3 distribution structure under 1 wt% SA conditions.

[0074] The peel performance of multilayer composite dressings was evaluated by combining a BATTAB absorbent layer with different functional contact layers. Tests were conducted both laterally and longitudinally to simulate multidirectional stress conditions in real-world use. Figure 9 As shown, the composite dressing has a smooth interface and intact structure before stretching; during stretching, the interface gradually deforms without instantaneous delamination or brittle fracture; after stretching, the whole remains continuous, indicating stable interlayer bonding (see...). Figure 9 (See section (d)). Peel strength results showed that all three composite dressings exhibited continuously fluctuating load curves, indicating that under the 1 wt% SA adhesive system and 4-3 distribution structure, interfacial failure was mainly point-by-point separation, and interlayer bonding was relatively uniform. Specifically, the BATTAB / QSA and BATTAB / QOSA / CMCS curves showed generally high levels and gentle fluctuations, indicating uniform interfacial bonding and stable adhesion; while the BATTAB / QSA / DHQ peel strength was generally low (see section (d)). Figure 9 In part (c) of the study, the interfacial bonding was relatively weakened, which may be related to its lower concentration. The peel strengths of the three components were 5.60, 5.10, and 2.80 N / 5cm, respectively (see [reference needed]). Figure 9 The results (part (a)) all exceed the requirements of standard T / YNIA 030-2025, indicating that reliable interfacial bonding can still be achieved with a lower adhesive dosage. Tensile strength test results show that the BATTAB / QSA composite dressing has the highest strength (280.0 N), while BATTAB / QOSA / CMCS and BATTAB / QSA / DHQ have strengths of 220.0 N and 210.0 N respectively (see [reference]). Figure 9 (Part (b) in the text) indicates that the multilayer composite structure has good overall mechanical properties and high structural stability.

[0075] (iv) Observation of the surface morphology of multilayer composite dressings Test method: The composite antibacterial dressing was analyzed using a SU3800 SEM (scanning electron microscope). After vacuum gold plating, images were acquired. The instrument's accelerating voltage was set to 10 kV, and the surface features and microstructure of the fibers were observed at different magnifications.

[0076] The microstructure and interlayer bonding characteristics of multilayer composite dressings are as follows: Figure 10 As shown. Figure 10 Part (a) shows the cross-sectional morphology of the BATTAB needle-punched absorbent pad, whose fibers exhibit a typical three-dimensional interlaced distribution, a relatively loose structure, and good pore connectivity. BATTAB / QSA, BATTAB / QOSA / CMCS, and BATTAB / QSA / DHQ composite dressings show continuous adhesive layers at the composite interface of the three dressings (as shown in the diagram). Figure 10 As shown in sections (b), (c), and (d), the SA adhesive forms an effective bridge between the two fiber layers, achieving a tight bond between the contact layer and the absorbent layer. It can be seen that in localized areas, the fibers of the contact layer and absorbent layer become entangled, thus forming a relatively uniform and stable interlayer bonding structure. Overall, each composite system maintains good interfacial integrity, providing support for the dressing in practical use.

[0077] (v) Pore size distribution test of multilayer composite dressing Test method: The pore size distribution of QSA composite dressings under different spraying concentrations was tested using a CFP-1500-A pore size analyzer. The pore size test results after lamination are as follows: Figure 11 As shown.

[0078] Under optimal bonding conditions, the pore size distribution of the multilayer composite dressing exhibits an approximately normal distribution, indicating that the bonding process did not cause pore structure collapse or a multi-peak structure, and the pore continuity is good (see...). Figure 11 As shown in sections (a), (b), and (c) of the diagram. The average pore size of the ATTAB / QSA composite dressing is 26.4 μm, mainly distributed between 10-40 μm; the average pore size of the BATTAB / QOSA / CMCS composite dressing decreases to 17.5 μm, concentrated between 15-30 μm, indicating that the cross-linked network has a stronger constraint effect on the pores, making the structure more compact; while the average pore size of the BATTAB / QSA / DHQ composite dressing is 29.5 μm, distributed between 20-50 μm, with relatively open channels, which is conducive to liquid permeation and gas exchange. Overall, while maintaining the continuity of the pores, different composite systems affect the liquid conduction and distribution behavior by changing the pore size and distribution characteristics, providing a structural basis for the coordination of liquid absorption and gas permeability.

[0079] (vi) Water absorption test of multilayer composite dressing Test Method: The prepared sprayed QSA composite dressing was placed in a constant temperature and humidity laboratory (temperature 25 ℃, relative humidity 60%) for 48 h to equilibrate and eliminate the influence of environmental differences on the sample state. Subsequently, the composite dressing was immersed in deionized water and phosphate buffered saline (PBS) solution at 37 ℃. After being removed at different times, the surface moisture was gently absorbed with filter paper, and the wet weight Ww was measured. The dressing was then dried in a vacuum oven at 50 ℃ until constant weight, recorded as the dry weight Wd. The swelling rate and water content of different composite dressings were calculated using the following formula: .

[0080] To analyze the impact of composite structures on the liquid absorption properties of materials, comparative tests were conducted on single-layer dressings and multi-layer composite dressings. The results are as follows: Figure 12 As shown, the swelling rates of the three different multilayer composite dressings did not show a significant decrease compared to the single-layer dressings (see Figure 1). Figure 12 As shown in section (a): the equilibrium swelling rates of BATTAB / QOSA / CMCS and BATTAB / QSA / DHQ are 12.5 g / g and 11.5 g / g, respectively, which are higher than those of BATTAB / QSA (9.5 g / g). This difference is mainly due to the different concentrations of the contact layer itself. For the BATTAB / QSA system, due to the higher QSA content in the contact layer, a relatively dense surface structure is easily formed during the composite process, which enhances the interlayer adhesion, thereby reducing the internal pore connectivity of the material and limiting the penetration and diffusion of liquid into the absorbent layer. In contrast, the contact layers of QOSA / CMCS and QSA / DHQ still maintain a relatively loose structure after composite, which is conducive to the diffusion and storage of liquid inside the material.

[0081] and Figure 12 The water content test results in Part (b) show that the water content of BATTAB / QSA, BATTAB / QOSA / CMCS and BATTAB / QSA / DHQ multilayer composite dressings reached 92.42%, 93.35% and 93.59% respectively. This confirms that the introduction of the needle-punched absorbent layer expands the liquid storage space of the system. The three-dimensional pore network between the layers of the multilayer composite dressing can enhance the retention and locking capacity of liquid inside the material, achieving a synergistic effect of swelling and efficient water retention.

[0082] This application presents a systematic study on the absorption layer structure, interface recombination mechanism, and pore structure control, and the results confirm that: (1) The structure of the needle-punched nonwoven absorbent layer has a significant impact on the liquid transport behavior. The comparison results of different structures show that the BATTAB sample has the highest unidirectional transport index (227.7), which is significantly better than other combinations; its porosity is 89.5%, which can realize unidirectional conduction and effective liquid storage of wound exudate, and is suitable as the absorbent layer of multilayer composite dressings.

[0083] (2) Under the conditions of 1wt% SA as adhesive, combined with square pressing and 4-3 distribution structure, the peel strength of the multilayer composite dressing is consistently higher than 1N / 5cm, meeting the relevant standard requirements. At the same time, the compaction effect on the fiber network is small under these conditions, which is conducive to preserving the original three-dimensional interconnected pore structure of the absorbent layer. The pore size distribution of the composite dressing after lamination shows an approximately normal characteristic, without obvious collapse or multi-peak structure, indicating that the composite structure has a significant impact on the overall pore continuity of the dressing. Different contact layer systems result in an average pore size distribution in the range of 17.5-29.5 nm. By adjusting the pore size and connectivity, the transport and distribution of liquid in the multilayer structure can be further affected.

[0084] (3) The results of the liquid absorption performance showed that the swelling rate of the three different multilayer composite dressings did not decrease significantly compared with that of the single-layer dressing. The equilibrium swelling rate of the multilayer composite dressings was 9.5-12.5 g / g. Relatively speaking, BATTAB / QOSA / CMCS and BATTAB / QSA / DHQ showed higher liquid absorption capacity, while BATTAB / QSA was relatively lower. This is mainly related to the higher QSA content in the contact layer, which leads to a denser structure and better pore connectivity. In addition, the water content of the BATTAB / QSA, BATTAB / QOSA / CMCS and BATTAB / QSA / DHQ multilayer composite dressings reached 92.42%, 93.35% and 93.59% respectively, which can effectively absorb and store wound exudate, and have a fast liquid absorption response and stable water retention capacity.

[0085] The above-described embodiments are merely illustrative of several feasible implementations of the present invention, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of the present invention, nor are the embodiments intended to limit the scope of protection in the claims of the present invention. For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention. All equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.

Claims

1. A highly absorbent, multi-layered composite antibacterial dressing, characterized in that: The contact layer is either QOSA / CMCS dressing or QSA / DHQ dressing, with a pore size of 17.5–29.5 µm. QSA refers to quaternized alginate, QOSA refers to quaternized oxidized sodium alginate, CMCS refers to carboxymethyl chitosan, and DHQ refers to dihydroquercetin. A needle-punched absorbent pad is used as the absorbent layer. The absorbent layer includes an intermediate layer and two viscose fiber layers located on both sides of the intermediate layer. The intermediate layer is made of hydroxymethyl cellulose fiber. The first viscose fiber layer contains viscose fibers of at least two finenesses, with the fineness decreasing from the outside to the inside. The second viscose fiber layer contains viscose fibers of at least two finenesses, with the fineness decreasing from the outside to the inside. The needle-punched absorbent pad is prepared as follows: S1, the fiber raw materials, including viscose fiber and hydroxymethyl cellulose fiber, are further opened, combed, and oriented in a carding machine to form a fiber web; after the fiber web enters the pre-needling zone for preliminary consolidation, it enters the main needle-punching zone, and the fiber web is double-sided entangled and reinforced under the cooperation of the main needles and barbs in the main needle-punching zone to obtain a single fiber nonwoven fabric corresponding to each fiber, wherein the fineness of the viscose fiber is 1-2 dtex and the fineness of the hydroxymethyl cellulose fiber is 1-1.5 dtex; S2, each single fiber nonwoven fabric is stacked and then needle-punched again to obtain a needle-punched absorbent pad; An adhesive layer is provided between the contact layer and the absorbent layer. The adhesive layer is a sodium alginate solution with a concentration of 1-2 wt%. The contact layer and the absorbent layer are constructed through interlayer composite to obtain a multi-layer composite antibacterial dressing with high liquid absorption. In the interlayer composite, pressure is applied by pressing columns arranged in a dot matrix. The applied pressure is 50-300 kPa and the pressure application time is 10-30 s.

2. The highly absorbent, multi-layered composite antibacterial dressing according to claim 1, characterized in that, In S1, The parameters for the combing process are set as follows: cylinder speed 35-45 r / min, doffer speed 8-12 r / min, fiber feed speed 5-15 m / min, upper and lower curtain conveying speeds 8-15 m / min, and matte curtain speed 3-6 m / min. The parameters of the pre-needling zone are set as follows: needle punching frequency 10-20 times / min, fiber web feeding speed 5-20 m / min, and discharge speed 5-20 m / min. The parameters of the main needle-punching area are set as follows: main needle-punching frequency 20-35 times / min, barb frequency 20-35 times / min, feeding speed 15-20 m / min, and discharging speed 15-20 m / min.

3. The highly absorbent, multi-layered composite antibacterial dressing according to claim 1, characterized in that, In S2, the parameters for the second needle piercing are set as follows: the pre-piercing frequency is 10-15 times / min, the feeding speed is 10-20 m / min, and the discharge speed is 10-20 m / min; the frequencies of the main piercing and the barbs are 30-35 times / min and 30-35 times / min, respectively, and the feeding and discharge speeds are both 15-20 m / min.

4. The highly absorbent, multi-layered composite antibacterial dressing according to claim 1, characterized in that: The dot matrix arrangement refers to the arrangement of multiple pressing columns in a staggered, upright, or random manner, with the pressing columns being cylindrical or square.

Citation Information

Patent Citations

  • Moisture-transfer and fast drying wound dressing

    CN105597136A